Debonding characteristics of orthodontic brackets subjected to intraoral stresses under different adhesive regimes: An in-vitro study. (April 2020) - Abdelaziz, Khalid M; Alshahrani, Ibrahim; Kamran, Muhammad Abdullah; Alnazeh, Abdullah
Aim: To evaluate the effect of simulated intraoral hydraulic, thermal, and mechanical stresses on the debonding characteristics of orthodontic brackets under different adhesive regimes. Materials and methods: Groups of pre-coated (G1) and non-coated (G2) orthodontic metal brackets were bonded onto the buccal surfaces of 96 premolars using etch-and-rinse (SG1, n = 24) and self-etch (SG2, n = 24) primers. Twelve specimens (C1) from each subgroup were subjected to early debonding resistance tests, while the other twelve (C2) were used to test delayed debonding resistance after exposure to conditions simulating intraoral hydraulic, thermal, and mechanical stresses. The debonding resistance of the brackets was evaluated using a universal testing machine and the debonding patterns were micro-visualized to determine the adhesive remnant indexes of subgroups of specimens. Results: Within each group, the etch-and-rinse primer (SG1) resulted in higher debonding resistance than self-etch primers (SG2) ( p < 0.05), while there was no difference between non-stressed and stressed specimens ( p > 0.05). Within each category of test specimens, there was no difference between pre-coated (G1) and non-coated (G2) brackets ( p > 0.05). The tested specimens in all categories showed comparable adhesive remnant indexes. However, higher percentages of favorable scores (0 and 1) were obtained for all stressed specimens. Conclusions: Short-term cumulative intraoral stresses have no adverse effect on the debonding values of either pre-coated or non-coated brackets when either etch-and-rinse or self-etch primer is used for bonding. Exposure of the bonded brackets to different types of stress reflects favorable debonding patterns.